The Framework of Modeling Buddhist Head in 3D with Semantic Information - Y. Pan; H. Li; H. Fan; B. Gu; X. Zhao; M. Hou (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Buddhist statues hold profound spiritual and cultural significance, yet their comprehensive analysis and identification remain largely reliant on manual annotation and expert scrutiny. Despite advancements in 3D modeling, the nuanced representation of these statues, essential for automated analysis, remains elusive. Integrating semantic information such as symbolic and cultural elements poses a further challenge. There currently exists no standardized method for modeling Buddhist heads in 3D with semantic information. This paper proposes a framework for the component-based analysis of Buddhist statues, particularly focusing on their heads, to bridge this gap. Drawing from diverse disciplines including archaeology, art history, and conservation, the framework leverages advancements in 3D reconstruction to provide a detailed depiction of intricate features. Building upon existing research outcomes, the framework facilitates the seamless integration of semantic information, capturing not only the physical attributes but also the cultural, historical, and spiritual dimensions of these sculptures. This approach aids in overcoming challenges in automated analysis and virtual restoration, providing a dynamic tool for exploration, preservation, and interpretation of cultural heritage. By enabling interdisciplinary synergy, the framework emerges as a dynamic tool for exploring, preserving, and interpreting the profound heritage of Buddhist art with unprecedented depth and clarity.